Teacher Capability in Developing Independent Curriculum Learning Tools - Munawarah, Munawarah; Nurhasanah, Nurhasanah; Zain, Mohammad Irawan (Yayasan Insan Mulia Bima, 2024)
The Merdeka Curriculum is the latest innovation that takes time for teachers to adjust their teaching methods. This study aims to analyze teachers' ability to develop learning tools in accordance with the Merdeka Curriculum at SD Negeri 32 Cakranegara. The focus of this research is on grade 4A and 4B teachers, using observation, documentation, and interview methods to collect data regarding teachers' competencies and their learning designs. The results showed that SDN 32 Cakranegara has implemented various concepts from Merdeka Belajar. Teachers demonstrate skills in designing learning tools such as teaching modules, Learner Worksheets (LKPD), media, teaching materials, and evaluations, in accordance with the required stages and components. However, in its implementation, there are challenges such as arranging the Flow of Learning Objectives (ATP) to be more organized and systematic. In addition, teachers also have difficulties in preparing the Learning Implementation Plan (RPP) and choosing appropriate assessments to evaluate learning. The limitations of student books, teachers' lack of ability and readiness to use varied learning methods and media, as well as limited technology skills, are also obstacles. The wide range of teaching materials and the difficulty in determining appropriate class projects in grade IV are also challenges. To overcome this, it is recommended that teachers seek additional references on learning assessment and attend training regularly to improve their competence.